Brown Marmorated Stink Bug, Halyomorpha halys (Stål) (Insecta: Hemiptera: Pentatomidae) - Amanda Hodges; Cory Penca (EDIS, 2019)
Contents:  Introduction - Synonymy - Distribution - Description - Life Cycle - Economic Importance - Hosts - Management - Brown Marmorated Stink Bugs in Florida - Selected References